IMPROVING EARLY CHILDHOOD NUMBERS ABILITY THROUGH NUMBER STICK MEDIA FOR CHILDREN AGED 4-5 YEARS - Enung Nurhayati, Dedi Aryadi, Yusdiana (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
The purpose of this study was to determine the strategy of playing stick numbers can improve early counting in BKB Melati Binuang District. From the results of cycle 1 research above, it can be concluded that out of 10 children, it is known that learning completeness in the ability to count the beginning has not reached the expected standard of 71%, it is evident from the average results obtained results of 66% of 10 children who are the object of research, children who get the highest score with a total score of 15 or 94%, and the lowest score with a total score of 8 or 50%. From the results of cycle 2 research above, it can be concluded that out of 10 children, it is known that learning completeness in the ability to count the beginning has reached the expected standard of 71%, it is evident from the average results obtained of 80%, out of 10 children who were the object of research, the child who obtained the highest score with a total score of 16 or 100%, and the lowest score with a total score of 11 or 69%. Based on the results of the study, it can be concluded that by using the number stick media from 10 children, it is known that the completeness of learning in the ability to count the beginning has reached the expected standard of 71%, it is evident from the average results obtained of 80%, from 10 children who were the object of research, the child who obtained the highest score with a total score of 16 or 100%, and the lowest score with a total score of 11 or 69%. at BKB Melati